Kebijakan Sekolah dalam Menerapkan Pendidikan Akhlak - Dertha Mukhtar; Saiful Anwar (JIE (Journal of Islamic Education), 2023)
This research was conducted to explain school policies in implementing moral education for students at SDN 10 Sungai Pasak, East Pariaman District. Through qualitative field study techniques, data were obtained by observation and interviews, data processing techniques by examining data, studying data in depth and drawing conclusions, data analysis techniques by adjusting the statements put forward by respondents to the problems studied. The results of the research that the authors got were the activities that the school carried out in implementing moral education for students at SDN 10 Sungai Pasak, East Pariaman District, that all students participated in all activities carried out by the school to foster student morals. The school's actions towards students who commit violations at SDN 10 Sungai Pasak, East Pariaman District are calling students who have problems, asking students' habits, giving directions, giving advice, giving educational punishments, and calling Siawa's parents. Factors supporting policy makers in implementing moral education are the existence of qualified teachers, the existence of extracurricular activities for Islamic religious education outside school hours and the existence of competitions. Factors hindering policy makers in implementing moral education are environmental factors where students live, the magnitude of the influence of technology, the lack of learning time and the lack of religious books as student reading.